Title: A Study on Production and Marketing of Pineapple in Kolli Hills, Namakkal District, Tamil Nadu-India. - Sivakkolundu, Dr. C.; P.Sheeba; M.Adhilakshmi (The journal of contemporary issues in business and government, 2021)
India is the second largest producer of fruits (44mt) and vegetables (87.5mt) with a unique position in fruits like mango, banana, pineapple, sapota and grapes. India’s share in the world production is about 10.1 per cent in fruits and 14.4 per cent in vegetables. The future of the Indian farmers depends on the success of the agriculture sector as India’s prosperity is predominantly linked to the growth in income in the agrarian sector. Pineapple is the most important American fruit and the third most important tropical fruit, after banana and mango. It is cultivated in all tropical and subtropical countries. The common name for one member of and for the Bromeliaceae. The fruit, whose spiny skin is yellowish brown when ripe, is sweet and juicy it is topped by a distinctive rosette of green leaves. It is grown throughout warmer regions. Pineapple is gradually expanding in the study area district.